Pelatihan Digital Marketing Produk UMKM Pada Masyarakat Desa Betek Guna Meningkatkan Kesejahteraan Masyarakat - Muhammad Farid Nasrulloh; Wisnu Mahendri; Khotim Fadhli; Muhammad Jafar Sodiq Maksum (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2023)
Electronic Commerce (e-commerce) is a new behavior that can be described as the process of transactions for goods or services in the process of buying and selling or exchanging products, services and information via information networks, including the internet or cyberspace, in line with the very rapid development of the internet world. Service implementers observed that marketing of UMKM products in Betek village, Mojoagung subdistrict is still limited and still uses the WoM (Word of Mouth) marketing method so that sellers only rely on buyers who come. The problem with partners is that marketing is still done traditionally, namely by word of mouth and only relies on consumers who come to get turnover and offers to close friends and the surrounding environment and there is a lack of understanding and use of digital marketing to increase sales. The problems faced must immediately find a solution. One alternative solution is to use digital marketing media. The objectives of this digital marketing-based UMKM product marketing assistance program are as follows: (1) UMKM owners in Betek village can increase their understanding of digital marketing; (2) UMKM owners in Betek village can increase the use of digital marketing more effectively; (3) MSME owners in Betek village can expand their marketing area; (4) Betek village UMKM owners can increase their income. With this digital marketing training, sales of Betek Village UMKM products increased by 60% from before the intensive assistance was implemented.